The association between the fibrinogen-to-albumin ratio and delirium after deep brain stimulation surgery in Parkinson’s disease - Lu, Wenbin; Wang, Hui; Lin, Shengwei; Chang, Xinning; Wang, Jiali; Wu, Xi; Yu, Xiya (Frontiers in Medicine, 2024)
Postoperative delirium (POD) remains one of the most prevalent neuropsychiatric complications after deep brain stimulation (DBS) surgery. The fibrinogen-to-albumin ratio (FAR) has been shown to significantly correlate with prognosis of many diseases related to inflammation. However, the association between FAR and POD remains unclear. We aimed to explore the association between POD and FAR in patients with Parkinson's disease (PD) undergoing DBS surgery.Methods: Patients with PD who underwent DBS surgery in our hospital were included in this retrospective study. FAR was calculated from the blood sample collected on admission. The association between baseline FAR and delirium after surgery was assessed by binary logistic regression analysis, interaction, and stratified analyses.Results: Of 226 patients, 37 (16.4%) suffered from delirium after surgery. The average age of the participants was 63.3 ± 7.2 years, and 51.3% were males. Multivariate logistic regression analysis indicated that patients in the highest FAR tertile had a higher risk of POD compared with patients in the lowest FAR tertile (OR = 3.93, 95% CI: 1.24~12.67). Subgroup analysis demonstrated that FAR and preoperative Mini-mental State Examination score (P = 0.013) had an interaction on delirium after surgery.Our data suggest that higher preoperative FAR was significantly associated with delirium after DBS surgery. FAR on admission is a useful candidate biomarker to identify patients with PD at a high risk of delirium following DBS surgery.